Transient liver elastography in unsedated control children: Impact of age and intercurrent illness. (20th May 2016) - Lewindon, Peter J; Balouch, Fariha; Pereira, Tamara N; Puertolas‐Lopez, Mora V; Noble, Charlton; Wixey, Julie A; Ramm, Grant A
Abstract : Aim: Transient elastography (TE) is a rapid, non‐invasive, reproducible assessment of liver fibrosis by liver stiffness measurement (LSM). Uncertainty remains regarding utility in children, unsedated and <6 years of age. The importance of general health at the time of study has not been addressed. We report our experience of TE in unsedated control children, impact of intercurrent illness and using new published reliability criteria. Methods: From April 2011 to March 2013, 173 studies were performed in unsedated, healthy control children and children with intercurrent illness without detectable liver disease presenting to the Royal Children's Hospital, Brisbane, Australia. LSM reliability was assessed using interquartile range/median (IQR/M ≤ 30%) of 10 valid measurements. Results: A total of 123 (F:M, 52:71) of 173 studies (71.1%) gave reliable results. In children 0–2 years reliability was 36%, and >2 years reliable results were obtained in ~80%. LSM increased with age; 0–2 years (3.5 ± 0.5 kPa), 3–5 years (3.8 ± 0.3 kPa) and 6–11 years (4.1 ± 0.2 kPa) with healthy older children 12–18 years similar to adults (4.5 ± 0.2 kPa). LSM did not vary with gender (female, 4.5 ± 0.2 vs. male, 4.8 ± 0.2 kPa). Children with intercurrent, non‐hepatological illnesses had higher LSM (5.2 ± 0.2 kPa (range, 2.8–11.1 kPa)) compared to healthy children ((4.1 ± 0.1 kPa, range, 2.1–6.3 kPa); P  = 0.0001). Conclusions: TE in unsedated children is feasible from infancy but most reliable after 2 years. Intercurrent illness increases LSM; hence, study context is important when interpreting results.